VD_FINDINFO AP / 2011 / 119 vom 18. März 2009 - VD Tribunal cantonal (2009)
DROIT TRANSITOIRE, DÉCISION DE RENVOI, APPRÉCIATION DES PREUVES, INTERDICTION DE L'ARBITRAIRE | 444 al. 1 ch. 3 CPC, 9 Cst., 107 al. 2 LTF, 111 al. 3 LTF, 132 al. 1 LTF, 405 al. 1 CPC (CH)